Perancangan Buku Saku Tentang Kesehatan Pertumbuhan Gigi Susu Dan Gigi Tetap Oleh Poli Gigi Puskesmas Ibun Untuk Orang Tua Yang Memiliki Anak Usia 1-10 Tahun Di Kabupaten Bandung - Banon Gilang Muhamad Kali Ichsan; Alzena Ayu Lestarie (Universitas Informatika dan Bisnis Indonesia, 2021)
Maintaining teeth's health is also important besides the body's health. Treating children teeth, being most important factor. Children dental health are really important for their growth. According Stella Listyani, teeth persistency are the main problem that mostly face with, especially on elementary school. Based on the background, so we're knowing that the formulation of the problem is how the design of the pocket's book about dental growth on deciduous teeth and permanent teeth of Dental Clinic on Puskesmas Ibun for The Parents who Has Children aged 1-10 on Kabupaten Bandung. This paper using mixed method. For overcame this problem, the pocket book were made for educating children added with illustration. Primary pocket of this book